'Gelukkig hij die uw kinderen zal grijpen' - H. G. L. Peels (Acta Theologica, 2002)
“Happy is he who seizes your infants…”. Hermeneutical and biblical-theological positioning of the Old Testament imprecations The Old Testament contains many prayers for the shaming,   punishment or destruction of the godless, especially in the Psalms. This imprecatory prayer, which still forms one of the most troublesome dimensions of Scripture for modern Bible-readers, is usually explained very negatively as a human but intolerable expression of personal or national rancour/hostility, and as such put in sharp contrast with the New Testament message of love for the enemy. This article makes a plea for a more hermeneutically responsible exegesis, by paying attention to the background, context and intention of the imprecatory prayer itself. After having delineated the indigenous horizon of interpretation of the Old Testament imprecatory prayers, a comparison with New Testament data is made, leading to the conclusion that on the one hand the condemnation of Old Testament imprecatory prayer from the perspective of New Testament ethics is incorrect, but on the other that it is also impossible within the New Testament situation to raise the imprecatory prayer in the same manner as was done by the psalmists of the Old Testament.